2017
DOI: 10.1182/bloodadvances.2017007773
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus envelope pseudotyped lentiviral vectors transduce quiescent human HSCs at an efficiency without precedent

Abstract: Key Points H/F-LVs permit very-high-level transduction of human HSCs, even in the complete absence of cytokine stimulation. H/F-LVs outperform VSV-G-LVs for efficient correction of Fanconi anemia patient cells in unfractionated BM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…An UCOE sequence(10) was added to the lentiviral vector pHRSIN-SFFV-eGFP(11) upstream of the SFFV promoter to produce pHUS-GFP vector. For the CAR-expression vector, GFP in pHUS-GFP was replaced by an anti-CD22 CAR (m971 ScFv) fused to 28z and BBz (Dr. Orentas, National Cancer Institute).…”
Section: Methodsmentioning
confidence: 99%
“…An UCOE sequence(10) was added to the lentiviral vector pHRSIN-SFFV-eGFP(11) upstream of the SFFV promoter to produce pHUS-GFP vector. For the CAR-expression vector, GFP in pHUS-GFP was replaced by an anti-CD22 CAR (m971 ScFv) fused to 28z and BBz (Dr. Orentas, National Cancer Institute).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of unstimulated HSCs, the transduction levels reached 70%. It was further demonstrated that these high levels were maintained or increased even after successive rounds of engraftment in NOD/SCIDγC −/− (NSG) mice [47]. These results indicated that high levels of HSCs were transduced.…”
Section: Pseudotyping Lvs With H and F Glycoprotein From Measles Virusmentioning
confidence: 90%
“…These two viruses are stable in human and macaque sera, giving them a great potential for in vivo gene therapy. They also recognize the sodium-dependent neutral amino acid transport (ASCT-2) in human cells, but only BaEV also recognizes ASCT-1, giving BaEV a wider tropism [47,52]. ASCT-1 and -2 receptors have a 57% identical sequence, and they are expressed in a wide number of cells.…”
Section: Pseudotyping Of Lvs With Baboon Endogenous Virus and Feline mentioning
confidence: 99%
“…Besides LV-mediated gene transfer, other vectors are being investigated, such as foamy viral vectors [225], and measles virus envelope pseudotyped LVs [226]. HDAd5/35++ vectors also represent a promising strategy-particularly of relevance for in vivo HSC transduction.…”
Section: Fanconi Anemiamentioning
confidence: 99%